Epidemiologi dan Dampak Ekonomi Penyakit Mulut dan Kuku pada Usaha Penggemukan Sapi Potong di Kabupaten Rembang Jawa Tengah - Permatasari, Erdyanti; Mariyono, Joko; Harjanti, Dian Wahyu (Jurnal Sain Peternakan Indonesia, 2024)
This research aims to analyze the economic impact of FMD on beef cattle fattening businesses in Rembang Regency. The research was conducted in Rembang Regency on a beef cattle fattening business with 115 respondents. Of these 115 respondents, 46 groups of farmers whose livestock were not affected by FMD and 69 groups whose livestock were affected by FMD. Based on the R/C ratio value for both the group not affected by FMD and the group affected by FMD, the R/C value is < 1; it is considered that fattening cattle during an FMD outbreak is not profitable. The research results showed that the average income difference before FMD (2021) and during the FMD outbreak (2022) in the group of cattle not affected by FMD was IDR. - 6,659,570.68, while in the group of cattle affected by FMD, the average income difference was Rp. -7,900,693,088. Thus, the income difference between the group not affected by FMD and those affected by FMD decreased by -15.07%. This research concluded that the outbreak of FMD in Rembang Regency had a significant impact on the beef cattle fattening business; therefore, it is necessary to take preventive measures to prevent the occurrence of FMD in the following year by monitoring livestock movements, increasing immunity through FMD vaccination, increasing the number of Animal Health Centre as the spearhead of animal health in the field, and cross-sectoral coordination and collaboration (One Health) to eradicate the FMD outbreaks.